Penilaian Kinerja Guru Dengan Metode Simple Additive Weighting Di Yayasan Al-Muawanah Tasikmalaya - Salim; Muslimah, Ajeng Sabarini; Ghozaly, Rija Muhamad (Cipasung Techno Pesantren: Jurnal Ilmiah, 2024)
The Al-Muawanah Tasikmalaya Foundation is one of the foundations located in Ciheras village, Sukanagara village, Tanjungjaya district. Based on the results of observations and interviews, the problems found were that there were still teachers who lacked discipline, and the way the material was delivered was less varied. Therefore, research was conducted on teacher performance assessment at the Al-Muawanah Tasikmalaya Foundation. The method used in this research is the simple additive weighting (SAW) method. Based on research using this method, performance scores for each teacher were obtained. The performance scores obtained can be used as a reference to increase work motivation, position promotions, rewards and sanctions.